Was tut ein Geschichtsschreiber?: Formen auktorialen Handelns in Lukian, De historia conscribenda - Kuhn-Treichel, Thomas (Philologus, 2020)
Lucian’s work De historia conscribenda not only presents reflections on how one should or should not write history, but also illustrates possible ways to represent the authorial activity of a historian (i. e. how one writes ‘metahistory’). In this, two basic forms can be distinguished, both of which can be understood from a narratological perspective as metalepses. In the first case, the historian is represented as the direct originator of the action; in the second he acts as a mere observer, but one who moves spatially in and with his action. Both forms of statement stand within traditions of motifs that can be traced from antiquity through to the modern era; yet Lucian nonetheless makes an innovative contribution by inscribing value judgements into the motifs. The result is the suggestion that the historian fulfils the role of observer, while the role of originator turns out to be more apt for the poet than for the historian. This permits far-reaching conclusions to be drawn about the conception of poetry and historiography as a whole.